Design and Evaluation of Reform Plan for Local Academic Nursing Challenges Using Action Research - Marziyeh Asadizaker, PhD; Zhila Abedsaeedi, PhD; Heidarali Abedi, PhD; Azadeh Saki, PhD (Elsevier, 2016)
Purpose: This study identifies challenges to the first nurse training program for undergraduate nursing students at a nursing and midwifery school in Iran using a collaborative approach in order to improve the program. Methods: Action research was used as a research strategy with qualitative content analysis and quantitative evaluation. The participants were 148 individuals from nursing academic and clinical settings, including administrators, faculty members, students, and staff nurses. We obtained approval from the research deputy and ethics committee of Shahid Beheshti University of Medical Sciences in Tehran, Iran for this study. Results: Lack of coherence in the educational program and implementation of the program, inadequate communication between management inside and outside the organization, insufficient understanding of situations by students, and improper control of inhibitors and use of facilitators in teaching and in practice were among the major challenges in the first training process in the context of this study. After classification of problems, the educational decision-making authorities of the school developed an operational program with stakeholder cooperation to plan initial reforms, implementation of reforms, reflection about the actions, and evaluation. Comparison of student satisfaction with the collaborative learning process versus the traditional method showed that except for the atmosphere in the clinical learning environment (p>.05), the mean differences for all dimensions were statistically significant. Conclusions: The results confirm the overall success of the revised partnership program, but stressed the need for further modification of some details for its implementation in future rounds.